Nuevas estrellas pre enanas blancas pulsantes de masa extremadamente baja descubiertas en el CASLEO - Corti, Mariela Alejandra (2016)
The Extremely Low Mass white dwarfs (ELM, M 0.18--0.20 M) could arise after the loss of large amount of mass suffered by a red giant star in a binary system. The low mass white dwarfs have become an important source of study because some of them are pulsating stars. The latter is an unprecedented opportunity to know their interior and the evolutionary channels leading to their origin, by employing asteroseismology. In this paper, we present photometric analysis of data obtained in the CASLEO (Complejo Astronómico El Leoncito) about four new pulsating stars, that according to their surface gravities and effective temperatures, would be pre-ELM white dwarf stars. With this discovery, the number of pulsating pre-ELM white dwarf stars known would increase to six members.